Autorzy:Jacek Lech
Wydawnictwo:GWO
Rok wydania:2015
Połącz równe wyrażenia.4.58 gwiazdek na podstawie 12 opinii

Połącz równe wyrażenia.

5Zadanie
6Zadanie
7Zadanie
8Zadanie
9Zadanie

Obliczenia:

Pierwsza kolumna:

`2x(3x-x^3)=6x^2-2x^4` 

`6x(1-2x)=6x-12x^2` 

`3(2x^2-x^3)=6x^2-3x^3` 

`-2x^2(3x-6)=-6x^3+12x^2` 

`(18x^3-12x^2):(-6)=-3x^3+2x^2` 

`-2x^2(3-3x)=-6x^2+6x^3` 

Druga kolumna:

`-3x(x^2-2x)=-3x^3+6x^2` 

`(12x^2-4x^4):2=6x^2-2x^4` 

`3x(2x^2-2x)=6x^3-6x^2` 

`(36x^2-18x):(-3)=-12x^2+6x` 

`-x(3x^2-2x)=-3x^3+2x^2` 

`-6x(x^2-2x)=-6x^3+12x^2`